2000
DOI: 10.1007/s004010051162
|View full text |Cite
|
Sign up to set email alerts
|

Unmyelinated nerve fiber degeneration in chronic inflammatory demyelinating polyneuropathy

Abstract: To determine whether unmyelinated nerve fibers escape degeneration as one might expect in an immune response exclusively directed at myelin, we performed a morphometric examination of unmyelinated axons and myelinated nerve fibers in sural nerve biopsy specimens of 14 patients with a chronic inflammatory demyelinating polyneuropathy (CIDP) and of 12 age-matched normal controls. The numbers of unmyelinated axons, myelinated nerve fibers, denervated Schwann cell units and collagen pockets were quantified and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The results of this exploratory study confirm that small fibers are also affected in CIDP 13,14,16 . Unmyelinated nerve fiber involvement in sural nerve biopsy 26,27 and a reduction in corneal nerve fiber parameters have already been shown in CIDP 14,28,29 …”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The results of this exploratory study confirm that small fibers are also affected in CIDP 13,14,16 . Unmyelinated nerve fiber involvement in sural nerve biopsy 26,27 and a reduction in corneal nerve fiber parameters have already been shown in CIDP 14,28,29 …”
Section: Discussionsupporting
confidence: 81%
“…The results of this exploratory study confirm that small fibers are also affected in CIDP. 13,14,16 Unmyelinated nerve fiber involvement in sural nerve biopsy 26,27 and a reduction in corneal nerve fiber parameters have already been shown in CIDP. 14,28,29 The first study evaluating skin biopsy in CIDP showed that IENFD in the distal legs of 18 CIDP patients was significantly reduced compared with healthy controls, and the decline was significantly associated with autonomic symptoms.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Axonal loss is usually considered as a secondary event in demyelinating disorders and its severity has implications for the diagnosis and prognosis; nevertheless recent studies indicate that axonal damage might also occur early in the disease ( 8 ). CIDP involves mainly myelinated fibers, but unmyelinated nerve fibers are also involved, probably due to a heterogeneous immunological pathogenesis and the severity of the inflammatory process ( 9 ).…”
Section: The Various Mechanisms Of Axonal Degeneration and Lossmentioning
confidence: 99%